Māori in video games - A digital identity - Mahuta, Dean (Te Kaharoa, 2012)
The indigenous image is becoming more present in the world of gaming. For many years, the ‘native’ has been cast in video games, typically playing the ‘barbaric enemy hoard’, or the ‘simple, nature-loving’ people who are only too eager to be ‘saved’ by the ‘fairer’ races. In the early years of video games, Native American images played the biggest part, in games such as, Custers Revenge, Mortal Kombat and Banjo Tooie. Recently, in an effort to teach people about Africa’s history, an online game, Africa, was created, where users were set in a 13th century African civilisation.  In 2003, Māori culture first appeared in the game, Mark of Kri, and more recently in Brink, a post-apocolyptic reality of Earth, where ‘kirituhi’ (a traditional form of body art revived by modern practitioners of ‘tā moko’, the traditional form of tattoing was an option during the character creation process.As the gaming industry becomes larger, gaming companies continue to search the globe for new and ‘exciting’ inspiration.  The Māori image, it seems, has inevitably been sucked into a digital space that, if left unchecked, will create an identity they have no say over.  In order for Māori to maintain a sense of ‘digital identity’, Māori must start participating and appropriating digital spaces, “. . . before the technologies are applied to them, and their culture, by another group” (Brown, 2007).